2020
DOI: 10.1111/ppc.12668
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment to life with metastatic cancer through psychodrama group therapy: A qualitative study in Turkey

Abstract: This study describes the experiences of patients with metastatic cancer participating in psychodrama group therapy.Design and Methods: This study was carried out at the cancer hospital of the university, Turkey. The sample consisted of patients with metastatic cancer who participated in 16 weekly psychodrama sessions of 3 h each. The study was analyzed using the NVivo 11 software, the sessions which summarize and code the interviews.Findings: Five main themes were identified: Anxiety of death, coping strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the validity analysis of the scale, factor analysis is carried out from several aspects of overseas Chinese returnees' entrepreneurship education, and the research content is determined according to the results (Dong et al, 2021;Songül and Bahar, 2021). The followings are the content of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…In the validity analysis of the scale, factor analysis is carried out from several aspects of overseas Chinese returnees' entrepreneurship education, and the research content is determined according to the results (Dong et al, 2021;Songül and Bahar, 2021). The followings are the content of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have addressed the meaning of life for cancer patients in the world. A study in Turkey showed that cancer patients with a greater belief in the meaning of life have higher levels of psychological resilience and experience less suffering in life [12]. Another study in Korea suggested that people with cancer seek positive meaning in life by promoting positive emotions and improving their lifestyles, and this gives them hope [13].…”
Section: Introductionmentioning
confidence: 99%